The first wave of COVID-19 and mental distress of physician residents in Brazil: a comparison between two cohorts - Mário Luciano de Mélo Silva Júnior; Arthur Violante Sapia; Jonas Marques Cavalcanti Neto; Nathallya Maria Gomes Barbosa; Victória Beatriz Costa Neiva; Euler Nicolau Sauaia Filho (Human Resources for Health, 2023)
Abstract Introduction The reorganization of healthcare systems to face the COVID-19 pandemic has led to concerns regarding psychological distress of healthcare workers, and training requirements of physician residents. Objective To assess the influence of COVID-19 pandemic on depression, anxiety, burnout and training schedules of residents. Methods Two independent cross-sectional studies (the first in November 2019 [control], the second in June 2020, during the first wave of COVID-19 pandemic) enrolling physician residents from Brazil, using online surveys. In each of them, we collected demographic and training program data, and assessed depression, anxiety and burnout through PHQ-2, GAD-2 and MBI (2-item version) scales, respectively. We controlled confounding variables with logistic regression analysis. Results The COVID-19 cohort (n = 524) presented a briefer workload and had at least 1 day off per week more frequently, in relation to the control cohort (n = 1 419). The majority of residents (464/524, 89.5%) had a reduction in their duty hours, and believed they would need an extra training period after the end of the pandemic (399/524, 76.2%). The frequency of depression increased (46.0% vs. 58.8%, aOR = 1.64, 95% CI = 1.32–2.05), anxiety did not change (56.5% vs. 56.5%, aOR = 1.24, 95% CI = 0.99–1.55) and burnout decreased (37.0% vs. 26.1%, aOR = 0.77, 95% CI = 0.60–0.99). Sensitivity analysis did not change these results. Conclusion Mental distress is frequent among residents and associated with both training program and social environments. The consequences of the COVID-19 pandemic on training requirements should be specifically addressed by supervisors and policymakers, in a case-by-case basis. Psychological support must be provided to healthcare workers.